(untitled) (Journal of the College of Basic Education, 2022)
R.V. Fuller in [5] introduced the concept of subcontinuous function and used it to obtain conditions implying continuity. In [9] R. E. Simthson extended this concept to multifunctions and used it to obtain a number of results on multifunctions, and also developed criteria under which a multifunction is upper semi continuous.In this paper we introduce the notion of s-subcontinuity for multifunction as a generalization of subcontinuity and use it to obtain many results on multifunction with s-closed graphs. Conditions implying upper semi continuity [8] for multifunction are derived.Several characterizations for upper semi-continuity and lower semi continuity [8] are obtained using filterbasis.